Cascade of Liquid-Phase Catalytic Transfer Hydrogenation and Etherification of 5-Hydroxymethylfurfural to Potential Biodiesel Components over Lewis Acid Zeolites - Jae, Jungho; Mahmoud, Eyas; Lobo, Raul F.; Vlachos, Dionisios G. (WILEY-V C H VERLAG GMBH, 2014)
We report a one-step process for the production of diesel fuel from biomass-derived 5-hydroxymethylfurfural (HMF). The reaction proceeds through the sequential transfer hydrogenation and etherification of HMF to 2,5-bis(alkoxymethyl)furan, a potential biodiesel additive, catalyzed by a Lewis acid zeolite, such as Sn-Beta or Zr-Beta. An alcohol is used as a hydrogen donor and as a reactant in etherification. This cascade reaction can selectively produce high yields of the biodiesel additive (>80% yield) from HMF with the Sn-Beta catalyst and secondary alcohols, such as 2-propanol and 2-butanol.
Keywords: MEERWEIN-PONNDORF-VERLEY; HIGH-QUALITY DIESEL; BIOMASS; EFFICIENT; CELLULOSE; FRUCTOSE; HEMICELLULOSE; DEHYDRATION; CONVERSION; ALCOHOLS